2010
DOI: 10.1200/jco.2010.28.9793
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Vaccination With a TLR9 Agonist Induces Systemic Lymphoma Regression: A Phase I/II Study

Abstract: A B S T R A C T PurposeCombining tumor antigens with an immunostimulant can induce the immune system to specifically eliminate cancer cells. Generally, this combination is accomplished in an ex vivo, customized manner. In a preclinical lymphoma model, intratumoral injection of a Toll-like receptor 9 (TLR9) agonist induced systemic antitumor immunity and cured large, disseminated tumors. Patients and MethodsWe treated 15 patients with low-grade B-cell lymphoma using low-dose radiotherapy to a single tumor site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
324
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 456 publications
(336 citation statements)
references
References 40 publications
10
324
0
2
Order By: Relevance
“…In line with this, we observed, within primary FL tumors harboring homozygous CREBBP mutations, that malignant B cells expressed ∼10-fold lower surface HLA-DR levels compared with nonmalignant counterparts from the same microenvironment. Interestingly, MHC class II deficit in CREBBP mutant cases could be overcome by stimulation with TLR ligand; a maneuver that has been used clinically to increase expression of costimulatory molecules and that has been shown to induce measurable clinical responses in a subset of FL patients (35). These observations add additional evidence supporting the importance of nonmalignant immune cells in these tumors (1-3) but provide the first evidence to our knowledge for CREBBP mutations contributing to immune evasion in FL.…”
Section: Discussionmentioning
confidence: 45%
“…In line with this, we observed, within primary FL tumors harboring homozygous CREBBP mutations, that malignant B cells expressed ∼10-fold lower surface HLA-DR levels compared with nonmalignant counterparts from the same microenvironment. Interestingly, MHC class II deficit in CREBBP mutant cases could be overcome by stimulation with TLR ligand; a maneuver that has been used clinically to increase expression of costimulatory molecules and that has been shown to induce measurable clinical responses in a subset of FL patients (35). These observations add additional evidence supporting the importance of nonmalignant immune cells in these tumors (1-3) but provide the first evidence to our knowledge for CREBBP mutations contributing to immune evasion in FL.…”
Section: Discussionmentioning
confidence: 45%
“…Other innate immune pathway activators are being tested in the clinic as single agents or in combination with other therapies, with the aim to boost anti-tumor T cell responses [110][111][112]. Similar to STING agonists, intratumoral injection of TLR agonists such as CpG-rich oligodeoxynucleotides (CpG ODN, PF-3512676) along with low-dose radiotherapy has shown clinical responses in patients with advanced non-Hodgkin's lymphoma in a phase I/II clinical study [113].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…These reagents were employed also in a recent phase I study of in situ vaccination, which consists of low-dose irradiation to a single lymphoma site, followed by intratumoral injection of CpG at the same site. The first results were encouraging and showed that the in situ vaccination was able to induce tumor-reactive CD8 + T cells [54]. In addition, incorporation of Id into cytokine-carrying liposomes has been proposed as a tool to enhance Id delivery [37].…”
Section: Introduction________________________________________________mentioning
confidence: 76%